2008
DOI: 10.1111/j.1365-2788.2008.01115.x
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive investigation of dysphagia in adults with intellectual disabilities

Abstract: Findings indicate that dysphagia is a significant issue for people with ID warranting further investigation. Practice implications detailed include increasing awareness of 'at risk' groups, changes in dysphagia with ageing, medication use and illness, and how findings can inform assessment and training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 44 publications
5
96
2
1
Order By: Relevance
“…l Despite aspiration being a frequent cause of emergency admission to hospital, as well as a cause of death, among adults with ID, it was not clear that annual health checks were specifically recording any issues around eating, drinking and swallowing. We estimated that 1 in 20 adults with ID had dysphagia recorded, lower than some estimates, 164 so the recent call for dysphagia-related questions to be included in the annual health check has merit.…”
Section: Discussionmentioning
confidence: 77%
“…l Despite aspiration being a frequent cause of emergency admission to hospital, as well as a cause of death, among adults with ID, it was not clear that annual health checks were specifically recording any issues around eating, drinking and swallowing. We estimated that 1 in 20 adults with ID had dysphagia recorded, lower than some estimates, 164 so the recent call for dysphagia-related questions to be included in the annual health check has merit.…”
Section: Discussionmentioning
confidence: 77%
“…For children with cerebral palsy those with dysphagia were more likely to choke with meals, with 2 or more episodes occurring in 3 months in 12/15 (80%) of those with dysphagia but in none of the children without dysphagia [53]. In a study of adults with dysphagia where risks were reported based on clinical, videofluoroscopic and case history information, 89/99 (89.9%) were classified as at high risk of asphyxia [23].…”
Section: Choking/asphyxiationmentioning
confidence: 99%
“…were classified as at high risk of dehydration, and 57/99 (57.6%) at high risk of poor nutritional status [23]. Finally, a study of adults with mealtime support needs based on questions about GP and hospital visits found that there were nutritional concerns …”
Section: Nutritional Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Two common conditions that have a higher incidence than the general population are epilepsy [5] and dysphagia [6]. Epilepsy can be defined as sudden uncontrolled episodes of excessive electrical discharges of brain cells.…”
Section: Intellectual and Developmental Disability Populationmentioning
confidence: 99%